ANALISIS FUNGSI SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN PEDAGANG KAKI LIMA (PKL) BERDASARKAN PERATURAN DAERAH KOTA BANDAR LAMPUNG NOMOR 08 TAHUN 2000 TENTANG PEMBINAAN UMUM, KETERTIBAN, KEAMANAN, KEBERSIHAN, KESEHATAN DAN KEAPIKAN DALAM WILAYAH KOTA B - OKTA AINITA (Law Faculty of Universitas Bandar Lampung, 2017)
Bandar Lampung Government Regulation Number 13 year 2013 about the Formation of Organization and Working Procedure of Government task force unit in Bandar Lampung regulates tasks and functions of Government task force unit in Bandar Lampung. Government task force unit has important roles in maintaining public security and orderliness and to enforce regional law products. According to that job descriptions, Government task force unitconducts disciplining actions upon any violation of public safety and orderliness as well as upon any regional law product.The research problem was the function of Government task force unit in disciplining small vendors and inhibiting factors for Government task force unit in disciplining small vendors.This research used normative and empirical jurisdiction and criminology approaches with primary and secondary data collected from literary study and from the field respectively. The researchersconcluded that the Bandar Lampung Regional Regulation was not yet optimal because Government task force unit had conducted its tasks to help the Major in safety and orderliness by enforcing the Regional Regulations but there were many stret vendors did not understand this Regional Regulation, yet they finally did this government policy with particular compensations.